Changes in numbers of epidermal cell adhesion molecules caused by oral cyclosporin in psoriasis. Issue 8 (August 1993) - Edwards, B D; Andrew, S M; O'Driscoll, J B; Chalmers, R J; Ballardie, F W; Freemont, A J
Abstract : AIM–To determine the effects of a three month course of low dose cyclosporin on the expression of epidermal cell adhesion molecules. METHODS–Eighteen patients with psoriasis were treated for 12 weeks with either 2.5 or 5 mg/kg/day of oral cyclosporin. Biopsy specimens taken from skin before, during, and after cyclosporin treatment were stained immunohistochemically for CD 54 (ICAM-1), CD 29 (beta-1 integrins), and CD18 (beta-2 integrins). RESULTS–There was a highly significant (p < 0.01) clinical response after 12 weeks of cyclosporin as assessed by the Psoriasis Area and Severity Index (PASI) score. The staining of CD 29 on keratinocytes of affected and unaffected psoriatic skin was not affected by cyclosporin. Epidermal CD54 was variably expressed in active psoriatic plaques and changed unpredictably after cyclosporin (p = NS). Staining for CD18 on large epidermal dendritic cells was reduced after cyclosporin (p < 0.02). The expression of CD18 by large epidermal dendritic cells during treatment correlated strongly with the PASI score at that time and one month after stopping cyclosporin (p < 0.02). CONCLUSIONS–Persistence of epidermal staining for CD 54 in psoriasis is compatible with a good clinical response to cyclosporin. Residual staining for CD 18 on large epidermal dendritic cells may be a useful marker for early clinical relapse.